(untitled) (JURNAL IBU DAN ANAK, 2022)
Hemoglobin level is the most easily used parameter in determining anemia status. According to the World Health Organization (WHO in 2016, the prevalence of anemia in the world ranges from 40-88%. Eggs are one of the foods that contain iron of 7.2 mg/grain, and papaya fruit contain vitamin C of 78 mg/100 gr. The purpose of the study was to determine the effect of giving boiled free-range chicken eggs and papaya fruit on increase hemoglobin levels in adolescents girls at the Tahfizh Al-Quds Islamic Boarding School In Pekanbaru City in 2021. This type of research is Quasi Experiment with One Group Pretest and Posttest. This research was conducted in January to May 2021 at the Tahfizh Al-Quds Islamic Boarding School In Pekanbaru City. The sample of this study of 15 people where the sample was taken using the purposive sampling technique. Data analysis used dependent T test with a significance level of 95%. The results showed that the average hemoglobin level in adolescent girls before being given boiled free-range chicken eggs and papaya fruit was 13.5gr/dL and after being intervention increased 14.2gr/dL. The P-value was 0.000. There is an effect of giving boiled free-range chicken eggs and papaya fruit to the increase in hemoglobin levels in adolescent girls at the Tahfizh Al-Quds Islamic Boarding School In Pekanbaru City.